Legal Protection For Banking Customers Due To Skimming Based On Statutory Regulations - Evita Tri Elandiah; Hurairah Hurairah; Widya Timur (JURNAL HUKUM SEHASEN, 2026)
Legal protection for banking customers due to skimming based on statutory regulations”. This thesis examines how legal protection for banking customers due to skimming is based on statutory regulations as evidenced by consumer protection theory, civil agreement theory. The type of research used by the author in examining the problems in this study is normative research. Normative research is a process to find legal rules, legal principles, and legal doctrines to answer the legal issues faced. From the results of the study, if a customer makes a transaction at an ATM, the bank will also check the CCTV on the ATM machine. From the CCTV footage that can be seen, it can be seen whether the customer has made the transaction or not. Then, after checking and proving that the incident was indeed a skimming crime, the bank must replace the amount of customer money that has been lost by following the procedures provided by the bank itself. However, if during the investigation it is found that the customer lost money due to the customer's own negligence, the bank cannot replace the losses experienced by the customer. Examples of customer negligence are not closing the ATM machine with their hands when entering the ATM PIN, then the ATM card is left in the ATM machine, the customer makes online purchases, fraud and so on. There are 2 Forms of Protection Law. Preventive legal protection and repressive legal protection. Preventive legal protection provides legal subjects with the opportunity to raise objections or express opinions before a government decision becomes final. Repressive legal protection aims to resolve disputes. Customers have the right to receive compensation for funds or accounts lost or stolen from the bank holding the deposit rights.